2017
DOI: 10.3390/en10070961
|View full text |Cite
|
Sign up to set email alerts
|

On the Response of Nascent Soot Nanostructure and Oxidative Reactivity to Photoflash Exposure

Abstract: Soot particles are a kind of major pollutant from fuel combustion. To enrich the understanding of soot, this work focuses on investigating detailed influences of instantaneous external irradiation (conventional photoflash exposure) on nanostructure as well as oxidation reactivity of nascent soot particles. By detailed soot characterizations flash can reduce the mass of soot and soot nanostructure can be reconstructed substantially without burning. After flash, the degree of soot crystallization increases while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the HRTEM images, a measure of the physical extent of the atomic carbon layer planes was presented as fringe length, and a value of curvature of the fringes arising from odd numbered five-and seven-membered ring structures was signed as fringe tortuosity [64][65][66][67][68][69]. It was reported that the fringe length and tortuosity obtained from HRTEM images could change with a long exposure time of the electron beam irradiation [70].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the HRTEM images, a measure of the physical extent of the atomic carbon layer planes was presented as fringe length, and a value of curvature of the fringes arising from odd numbered five-and seven-membered ring structures was signed as fringe tortuosity [64][65][66][67][68][69]. It was reported that the fringe length and tortuosity obtained from HRTEM images could change with a long exposure time of the electron beam irradiation [70].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The image processing method, consisting of digital image processing and fringe characterization, was similar to the one developed by Maria and Yehliu et al [64][65][66][67]. The image processing run in MATLAB (2014) software with customized algorithms including several operations, such as negative transformation, region of interest selection, contrast enhancement, Gaussian lowpass filter, top-hat transformation, thresholding to obtain a binary image, morphological modification, skeletonization, and short fringes and boundary fringes removal.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Vander Wal further explored the impact of soot nanostructure covering fringe length, tortuosity and interval space of the carbon lamellae on soot oxidation behavior and illustrated that soot which showed higher oxidation rates had shorter fringe length and larger tortuosity and interval space. Numerous recent studies have also been conducted to investigate the relation between soot nanostructure and oxidation rate, and all concluded soot reactivity strongly depended on initial soot nanostructure. …”
Section: Introductionmentioning
confidence: 99%